Growth performance and leaf ecophysiological traits in three Aquilaria species in Malaysia - Kenzo, Tanaka; Yoneda, Reiji; Oda, Ayumi Tanaka; Azani, Mohamad Alias (Springer Dordrecht, 2019)
The genus Aquilaria (Thymelaeaceae) is widely used for the production of agarwood, and includes several valuable plantation species in Southeast Asia. To understand appropriate planting conditions, it is necessary to characterize species-specific ecological traits such as photosynthesis and drought tolerance among Aquilaria species. To this end, we measured leaf morphological and photosynthetic traits among three Aquilaria seedlings (A. hirta, A. malaccensis, A. subintegra) in Malaysia. We also monitored changes in growth and survival in a shaded nursery and 7 and 18 months after transfer to open conditions. To avoid transplant stress, the seedlings were kept in polybags. The highest leaf cuticle and epidermis layer ratio, leaf mass per area, and long-term water use efficiency indicated by δ13C were recorded in A. hirta, suggesting that this species had relatively high drought tolerance. By contrast, the high maximum photosynthetic rate and high stomatal conductance observed in A. subintegra explained their high growth rate, although their drought tolerance was the lowest among the studied species. A. malaccensis was considered an intermediate species in terms of photosynthesis and drought tolerance. Interspecific differences in growth and survival were present after transfer to open conditions. A. hirta had the lowest growth rate and highest survival rate (50% survival after 18 months), whereas A. subintegra had the highest growth rate and lowest survival rate (9% survival after 18 months). A. malaccensis was intermediate between the two. In summary, the studied Aquilaria species were susceptible to stress under the open and dry conditions of our study. This includes Aquilaria hirta, the most drought-tolerant species in this group, and A. subintegra, the most vulnerable species to drought, which may require careful management when planted in open conditions.